(untitled) (African Human Mobility Review, 2021)
The economic meltdown and worsening levels of poverty in Zimbabwe led to a significant increase in the number of women migrating to South Africa from 2005 to 2010 (Crush et al., 2015: 367). A Southern African Migration Programme (SAMP) survey in 1997 found that 61% of Zimbabwean migrants were male and 39% were female (Crush et al., 2015: 367). This suggested that there was an increase in the number of women migrating to South Africa compared with other countries in Southern Africa. This gives us reason to ‘speculate’ that the numbers could have increased a decade later because of the economic crisis that resulted in large numbers of people migrating out of Zimbabwe. Most Zimbabwean women are now moving across borders independently of their spouses and partners in search of better and sustainable livelihoods (Dzingirai et al., 2015: 13; Mbiyozo, 2019). Whilst some have valid immigration documents, a large number of these women are undocumented, which heightens their vulnerability to various structures of violence (Bloch, 2010; Rutherford, 2020: 172).